Recent Advances in Quantum Effects of 2D Materials. Issue 5 (14th May 2019) - Yi, Ya; Chen, Zhanxu; Yu, Xue‐Feng; Zhou, Zhang‐Kai; Li, Jia
Abstract: The celebrated discovery of graphene has spurred tremendous research interest in two‐dimensional layered materials (2DLMs) with unique attributes in the quantum regime. In 2DLMs, each layer is composed of a covalently bonded lattice and is weakly coupled to its neighboring layers by van der Waals interactions. There are abundant members in this 2DLM family beyond graphene, such as transition metal dichalcogenides (MX2, M = Mo, W; X = S, Se, Te), semimetal chalcogenide (InSe), black phosphorus, etc. The 2DLMs afford rich and ideal material platforms for studying quantum effects and their corresponding applications in the two‐dimensional (2D) limit. In this review, the emerging quantum effects in 2DLMs are examined with particular focus on their band structure evolvement, valleytronics, and quantum Hall/quantum spin Hall effects. Based on the summary of quantum effects discovered in 2DLMs, the future research directions and prospective applications are also discussed. Abstract : This review summarizes the emerging quantum effects in two‐dimensional (2D) materials, which are caused by quantum behaviors of the 2D electrons from three main perspectives including the evolution of electronic band structure, electronic polarization, and electronic transport. Thereby, the electronic band evolvement, valleytronics, quantum Hall/quantum spin Hall effects, along with prospective applications and future directions are introduced in succession.